SPECTROSCOPICAL STUDY OF FAINT SOUTHERN CEPHEIDS WITH SOUTHERN AFRICAN LARGE TELESCOPE (SALT). FIRST RESULTS. - Usenko, I. A.; Kniazev, A. Yu.; Kovtyukh, V. V.; Belik, S. I.; Berdnikov, L. N. (Одеські астрономічні публікації, 2017)
First Cepheids observations using echelle-spectrograph HRS fed by Southern African Large Telescope (SALT) were realized during 2016. All spectra have been obtained in the medium resoltion mode (R≈31000–41000) wth high S/N ratio near 50–220. All data were processed using package developed by authors based on the standard system of astronomical data reduction MIDAS. Using new echelle data we found the atmosphere parameters and chemical composition for 30 faint Cepheids of southern hemisphere, where for the most of theses stars these results we obtained for the ﬁrst time. 28 stars are Cepheids after the ﬁrst-dredge up stage, while ASAS 075842-25336.1 and ASAS 1131714-6605.0 having remarkable Li I 6707.8 Å absorption line and anomalous CNO and Na content could be consider as ﬁrst crossing of the Cepheids instability strip.